1992
DOI: 10.1042/bj2880959
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid metabolism. 7α-Hydroxylation of dehydroepiandrosterone and pregnenolone by rat brain microsomes

Abstract: Two 'neurosteroids', dehydroepiandrosterone (DHEA) and pregnenolone (PREG), are converted by rat brain microsomes into polar metabolites, identified as the respective 7 alpha-hydroxylated (7 alpha-OH) derivatives by the 'twin ion' technique of g.l.c.-m.s. with deuterated substrates. The enzymic reaction requires NADPH and is stimulated 2-4-fold by EDTA. Under optimal conditions (pH 7.4, 0.5 mM-NADPH, 1 mM-EDTA), the Km values for DHEA and PREG are 13.8 and 4.4 microM respectively, and the Vmax. values are 322 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 23 publications
6
79
1
1
Order By: Relevance
“…The verified occurrence of DHEA 7a-hydroxylase and DHEA 17-ketosteroid reductase activity in the human temporal lobe (Figs 2, 4 and 5) is in accordance with results obtained from rodent brain tissue experiments (Akwa et al 1992;Doostzadeh et al 1997;Rose et al 1997;Fig. 6).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The verified occurrence of DHEA 7a-hydroxylase and DHEA 17-ketosteroid reductase activity in the human temporal lobe (Figs 2, 4 and 5) is in accordance with results obtained from rodent brain tissue experiments (Akwa et al 1992;Doostzadeh et al 1997;Rose et al 1997;Fig. 6).…”
Section: Discussionsupporting
confidence: 89%
“…Within the rodent brain, DHEA is also known to be converted into 7b-hydroxy-DHEA (Akwa et al 1992;Doostzadeh et al 1997). According to this, we observed the formation of low amounts of a third polar metabolite when investigating mouse brain tissue homogenates (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…DHEA, pregnenolone and 5-Adiol are readily hydroxylated at C7 (Akwa et al, 1992;Lathe, 2002;Lardy, 2003). Moreover, these 7 -11 hydroxy-and 7 -hydroxy-steroids can be oxidized to 7-oxo-steroids [ Figure 4].…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…24-Hydroxylated cholesterol, which is a possible precursor of 3 ␤ -hydroxy-5-cholenoic acid, has been detected at very high levels in the brain (7). In addition, Akwa et al (8) have demonstrated that conversion of two neurosteroids, dehydroepiandrosterone and pregnenolone, into the corresponding 7 ␣ -hydroxylated derivatives occurs in rat brain microsomal fractions. In addition, in an older publication, 3 H-labeled 3 ␤ -hydroxy-5-cholenoic acid was metabolized into lithocholic acid when incubated with normal guinea pig brain preparations (9).…”
mentioning
confidence: 99%